Pengaruh Urbanisasi Terhadap Konsumsi Energi di Indonesia - Reza Novita Sari; Yollit Permata Sari (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Energy consumption is a vital aspect in sustainable development that is influenced by various factors, including urbanization, population, and economic growth. This study aims to analyze the effect of urbanization, population, and economic growth on energy consumption in Indonesia during the period 1965–2023. Secondary data were obtained from Ener Data and the World Bank, including energy consumption, urbanization rate, population size, and economic growth. The analysis was conducted using time series data regression, after passing the stationarity test, and classical assumptions. The results showed that urbanization had a negative and significant effect on energy consumption with a regression coefficient of -7.280276 and a p-value of 0.000. Population had a positive and significant effect with a regression coefficient of 20.89002 and a p-value of 0.000. Economic growth had a positive and significant effect on energy consumption with a coefficient of 14.77433 and a p-value of 0.000. These findings emphasize the importance of energy efficiency in dealing with population growth and urbanization dynamics in Indonesia.